ANALYSIS OF IDEAL LEGAL PROTECTION FOR WORKERS FOLLOWING THE ENACTMENT OF THE OMNIBUS LAW CONCERNING JOB CREATION - Suud, Aghia Khumaesi (Fakultas Syariah, 2023)
This article aims to discover the ideal form of protection for workers after the Job Creation Omnibus Law was passed, scrapping several articles such as articles 161, 164, 165, and 167 of Law Number 13 of 2003 concerning Employment which were considered detrimental to workers. This study seeks to provide recommendations for the ideal form of regulation for the protection of local workers by employing a juridical approach based on juridical reviews and statutory regulations using secondary data. For this reason, regulations regulating these matters are needed as ideal protection based on an agreement binding the parties, business entities, and workers to satisfy all their rights and obligations, thereby ensuring that good working relationships are established and prosperity is achieved. Business entities must work in tandem with individuals in fulfilling their rights and obligations according to the mandate of the 1945 Constitution. Apart from that, the author hopes that the government will consider amendments to the Job Creation Law by adding articles that support and provide protection for workers to bring about welfare without further thought at a global level. Artikel ini bertujuan untuk mencari bentuk perlindungan ideal kepada para pekerja pasca disahkannya Undang-Undang Omnibus Law Cipta Kerja yang menghapus beberapa pasal seperti pasal 161, 164, 165, 167 Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan yang dinilai merugikan pekerja. Kajian ini mencoba memberikan rekomendasi bentuk peraturan yang ideal untuk perlindungan pekerja local yang disajikan dengan menggunakan pendekatan yuridis berdasarkan tinjauan yuridis dan peraturan perundang-undangan dengan menggunakan data sekunder. Untuk itu, diperlukan peraturan yang memuat perlindungan ideal berdasarkan kesepakatan berupa perjanjian para pihak, badan usaha, dan pekerja untuk memenuhi seluruh hak dan kewajibannya sehingga dapat terjalin hubungan kerja yang baik dan tercapai kesejahteraan. Jadi, tidak hanya terfokus pada badan usaha saja melainkan antara badan usaha dan perseorangan yang harus saling bekerjasama dalam memenuhi hak dan kewajibannya sesuai amanat UUD 1945. Selain itu, hasil penelitian ini diharapkan bagi pemerintah untuk merevisi Undang-Undang Cipta Kerja dengan menambahkan pasal-pasal yang memihak dan memberikan perlindungan bagi pekerja untuk mendapatkan kesejahteraan tanpa berpikir berlebihan secara global.